Evaluation of tumour marker utilisation and impact of electronic gatekeeping in the province of KwaZulu-Natal, South Africa - Immaculate S. Dlamini; Verena Gounden; Nareshni Moodley (AOSIS, 2023)
Background: Inappropriate testing remains a high healthcare cost driver. Tumour marker tests are more expensive than routine chemistry testing. Implementing test demand management systems like electronic gatekeeping (EGK) has reportedly decreased test requests. Objective: This study aimed to describe the appropriateness of tumour marker tests, carcinoembryonic antigen, alpha foetal protein, prostate-specific antigen, carbohydrate antigen 19-9, cancer antigen 15-3, cancer antigen 125, and human chorionic gonadotropin, and determine the effectiveness of the EGK used in the public health sector in KwaZulu-Natal, South Africa. Methods: Tumour marker test data for the KwaZulu-Natal province were extracted from the National Health Laboratory Service Central Data Warehouse for 01 January 2017 - 30 June 2017 (pre-EGK) and 01 January 2018 - 30 June 2018 (post-EGK implementation). Questionnaires were sent to the clinicians in the regional hospitals ordering the most tumour marker tests to assess ordering practices. In addition, we assessed monthly rejection reports to determine the effect of the EGK. Results: The EGK minimally reduced tumour marker requests or associated costs (1.4% average EGK rejection rate). An overall 18% increase in the tumour marker tests occurred in 2018. The data suggest inappropriate tumour marker test utilisation, particularly for screening. Conclusion: The introduction of EGK as a test demand management had little impact on tumour marker test requests and costs. Continuous education and reiteration of indications for tumour marker test use are required. What this study adds: This study demonstrates the ineffectiveness of EGK in tumour marker orders, and provides some insight as to why these markers are being ordered, which is important in trying to decrease inappropriate ordering of these tests.